1979
DOI: 10.1136/hrt.42.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haemodynamic effects of oral hydralazine and prazosin hydrochloride in patients with chronic congestive heart failure.

Abstract: suMMARY The comparative haemodynamic effects of oral prazosin hydrochloride and hydralazine were evaluated in 11 patients with chronic congestive heart failure.The maximum total dose of prazosin received by an individual varied up to 25 mg. Ten patients received a maximum of 75 mg and one received 50 mg of hydralazine at six-hour intervals. There was no significant change in heart rate with either drug. Decrease in mean arterial and left ventricular filling pressures were modest and similar with both agents. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The underlying cardiac diseases in our patients were ischemic heart disease and cardiomyopathy as in other reports ( 1 , 8, I I , 12). Although higher doses have been administered in some studies (8, 12), a favourable effect of prazosin in doses comparable to ours has been demonstrated ( I , 6,11,14). It is, however, noteworthy that we administered prazosin as tablets whereas others have mostly used capsules ( I , 14).…”
Section: Discussionsupporting
confidence: 72%
“…The underlying cardiac diseases in our patients were ischemic heart disease and cardiomyopathy as in other reports ( 1 , 8, I I , 12). Although higher doses have been administered in some studies (8, 12), a favourable effect of prazosin in doses comparable to ours has been demonstrated ( I , 6,11,14). It is, however, noteworthy that we administered prazosin as tablets whereas others have mostly used capsules ( I , 14).…”
Section: Discussionsupporting
confidence: 72%
“…Agents that selectively vasodilate the arterial resistance vessels increase SV and CO but have little if any impact on ventricular filling pressures and the degree of congestion (2,3). Agents that increase venous capacitance and reduce ventricular afterload significantly reduce ventricular diastolic volume and pressure and the degree of congestion while increasing SV and CO (3).…”
Section: Circulatory Physiologymentioning
confidence: 99%